Activation of X–H Bonds (X = N, P, O, S) with SCS Pincer Palladium Complexes: A Theoretical Study. Issue 22 (13th June 2013) - Nicolas, Emmanuel; Martin‐Vaca, Blanca; Mézailles, Nicolas; Bourissou, Didier; Maron, Laurent
Abstract: Activation of X–H bonds with SCS pincer palladium complexes featuring methanediide and indenediide backbones was studied by DFT calculations. Me2 NH, Me2 PH, MeOH, MeSH, PhOH, and PhSH were chosen as model substrates. Different products were considered for these addition reactions: simple adduct (X coordination), 1, 2‐addition across the Pd–C and Pd–S bonds, 1, 3‐addition (if possible), as well as oxidative addition at Pd. For the methanediide system, 1, 2‐PdC adducts were predicted to be the most favored activation products. For the indenediide system, 1, 3‐PdC and 1, 2‐PdC additions are conceivable. This theoretical study suggests that methanediide and indenediide Pd complexes may be interesting candidates for catalytic transformations involving X–H bond activation, typically hydrofunctionalization reactions. Abstract : Coordination versus bond activation of several X–H substrates was studied by DFT calculations for SCS pincer palladium complexes featuring methanediide and indenediide backbones.